A synergistic effect of the ion beam sputtered NiOx hole transport layer and MXene doping on inverted perovskite solar cells. (15th October 2022) - Din, Muhammad Faraz Ud; Held, Vladimir; Ullah, Sami; Sousani, Shima; Omastova, Maria; Nadazdy, Vojtech; Shaji, Ashin; Siffalovic, Peter; Jergel, Matej; Majkova, Eva
Abstract: The synergistic effect of high-quality NiO x hole transport layers (HTLs) deposited by ion beam sputtering on ITO substrates and the Ti3 C2 T x MXene doping of CH3 NH3 PbI3 (MAPI) perovskite layers is investigated in order to improve the power conversion efficiency (PCE) of p-i-n perovskite solar cells (PSCs). The 18 nm thick NiO x layers are pinhole-free and exhibit large-scale homogeneous surface morphology as revealed by the atomic force microscopy (AFM). The grazing-incidence x-ray diffraction showed a 0.75% expansion of the face-centered cubic lattice, suggesting an excess of oxygen as is typical for non-stoichiometric NiO x . The HTLs were used to fabricate the PSCs with MXene-doped MAPI layers. A PSC with undoped MAPI layer served as a control. The size of MAPI polycrystalline grains increased from 430 ± 80 nm to 620 ± 190 nm on the doping, as revealed by AFM. The 0.15 wt% MXene doping showed a 14.3% enhancement in PCE as compared to the PSC with undoped MAPI. The energy-resolved electrochemical impedance spectroscopy revealed one order of magnitude higher density of defect states in the band gap of MXene-doped MAPI layer, which eliminated beneficial effect of reduced total area of larger MAPI grain boundaries, decreasing short-circuit current. The PCE improvement is attributed to a decrease of the work function from −5.26 eV to −5.32 eV on the MXene doping, which increased open-circuit voltage and fill factor.